Nice guys finish last: Are people with higher tax morale taxed more heavily? - Philipp Doerrenberg; Denvil Duncan; Clemens Fuest; Andreas Peichl (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper provides evidence of efficient taxation of groups with heterogeneous levels of tax morale. We set up an optimal income tax model where high tax morale implies a high subjective cost of evading taxes. The model predicts that nice guys finish last: groups with higher tax morale will be taxed more heavily, simply because taxing them is less costly. Based on unique cross-country micro data and an IV approach to rule out reverse causality, we find empirical support for this hypothesis. Income groups with high tax morale systematically face higher average and marginal tax rates. To the best of our knowledge, this is the first paper to investigate whether differences in tax morale affect the distribution of the tax burden across different groups of taxpayers.
Keywords: H20; H30; D70; 330; tax morale; tax compliance; optimal taxation; political economy; Steuermoral; Steuerbelastung; Optimale Besteuerung; Public Choice; Schätzung; Welt